2017
DOI: 10.1007/s11427-017-9026-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived phosphocholine facilitates cellular uptake of anti-pulmonary fibrotic HJT-sRNA-m7

Abstract: Pulmonary fibrosis, a progressive chronic disease with a high mortality rate, has limited treatment options. Currently, lung transplantation remains the only effective treatment. Here we report that a small RNA, HJT-sRNA-m7, from a Chinese herbal medicine Hong Jing Tian (HJT, Rhodiola crenulata can effectively reduce the expressions of fibrotic hallmark genes and proteins both in alveolar in vitro and in mouse lung tissues in vivo. We also discovered over one hundred oil-soluble chemicals from HJT decoctions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 25 publications
1
51
0
6
Order By: Relevance
“…one-to-one or one-to-multiple mapping between herbs and target tissues. xenomiRs have been shown to be the active ingredient in many traditional medical herbs [15-17, 21] and the tissue-specificity of xenomiRs coincide well with the theory of channel tropism. This research takes the first step to study the theory of channel tropism by showing the existence of the possible patterns in xenomiRs.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…one-to-one or one-to-multiple mapping between herbs and target tissues. xenomiRs have been shown to be the active ingredient in many traditional medical herbs [15-17, 21] and the tissue-specificity of xenomiRs coincide well with the theory of channel tropism. This research takes the first step to study the theory of channel tropism by showing the existence of the possible patterns in xenomiRs.…”
Section: Discussionmentioning
confidence: 84%
“…Many identified functions of xenomiRs have already been reported by other studies with bio-experiments. For example, xenomiRs were reported to be related with cancer [12, 13], inflammatory [15, 17], circulation system [7] in human body. And recent studies reported an association between xenomiRs with neuron development of pandas [10], and the caste development of honeybees [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…D in China, and it was used to cure liver and spleen ailments by the Arabian physicians during the 10th and 11th centuries. Accumulating evidence indicates that taraxacum officinale extract (TOE) exhibits various biological activities, such as anti‐inflammatory, antioxidant and antifibrotic activities, and possess the properties against type 2 diabetes, non‐alcoholic fatty liver disease (NAFLD), obesity and cancers . However, there is little knowledge about the effects of TOE on acute colitis.…”
Section: Introductionmentioning
confidence: 99%